Specificity of Youth Slang in the Public Discourse of the English Language - Lutfullaevna, Talibjanova Aziza (Miasto Przyszłości, 2023)
The article considers about specificity of youth slang in the public discourse of the English language. Here are some examples of slangs from youth language given and analyzed as well.